Embedded pair of diagonally implicit Runge-Kutta method for solving ordinary differential equations - Fudziah Ismail; Raed Ali Al-Khasawneh; Mohamed Suleiman; Malik Abu Hassan (Universiti Kebangsaan Malaysia, 2010)
Improvements over embedded diagonally implicit Runge-Kutta pair of order four in five are presented. Method of higher stage order with a zero first row and the last row of the coefficient matrix is identical to the vector output is given. The stability aspect of it is also looked into and a standard test problems are solved using the method. Numerical results are tabulated and compared with the existing method.